2010
DOI: 10.1007/s12601-010-0015-2
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved organic phosphorus utilization and alkaline phosphatase activity of the dinoflagellate Gymnodinium impudicum isolated from the South Sea of Korea

Abstract: This study investigated alkaline phosphatase (APase) activity and dissolved organic and inorganic phosphorus utilization by the harmful dinoflagellate Gymnodinium impudicum (Fraga et Bravo) Hansen et Moestrup isolated from the South Sea of Korea. Under conditions of limited phosphorus, observation of growth kinetics in batch culture yielded a maximum growth rate (µ max ) of 0.41 /day and a half saturation constant (Ks) of 0.71 µM. In time-course experiments, APase was induced as dissolved inorganic phosphorus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 44 publications
0
15
1
Order By: Relevance
“…phosphate (MFP) (Ou et al, 2008), methylumbelliferyl phosphate (MUF-P) (Jauzein et al, 2010), pNPP (Kruskopf and Plessis, 2004), or disodium phenylphosphate (Oh et al, 2010) as substrate. APA varied greatly among microalgal species, such as 10-13.4 fmol/(cell·min) (600-804 fmol/(cell·hr)) for toxic dinoflagellate Alexandrium catenella using MUF-P as substrate (Jauzein et al, 2010), 1-3 fmol/(cell·hr) for Prorocentrum donghaiense, and maximum to 150 fmol/(cell·hr) for Alexandrium catenella, less than 2 fmol/(cell·hr) for the diatom Skeletonema costatum using MFP as substrate (Ou et al, 2008), and 0.02-0.7 pmol/(cell·hr) (20-700 fmol/(cell·hr)) for Gymnodinium impudicum using disodium phenylphosphate as substrate (Oh et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…phosphate (MFP) (Ou et al, 2008), methylumbelliferyl phosphate (MUF-P) (Jauzein et al, 2010), pNPP (Kruskopf and Plessis, 2004), or disodium phenylphosphate (Oh et al, 2010) as substrate. APA varied greatly among microalgal species, such as 10-13.4 fmol/(cell·min) (600-804 fmol/(cell·hr)) for toxic dinoflagellate Alexandrium catenella using MUF-P as substrate (Jauzein et al, 2010), 1-3 fmol/(cell·hr) for Prorocentrum donghaiense, and maximum to 150 fmol/(cell·hr) for Alexandrium catenella, less than 2 fmol/(cell·hr) for the diatom Skeletonema costatum using MFP as substrate (Ou et al, 2008), and 0.02-0.7 pmol/(cell·hr) (20-700 fmol/(cell·hr)) for Gymnodinium impudicum using disodium phenylphosphate as substrate (Oh et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…APA varied greatly among microalgal species, such as 10-13.4 fmol/(cell·min) (600-804 fmol/(cell·hr)) for toxic dinoflagellate Alexandrium catenella using MUF-P as substrate (Jauzein et al, 2010), 1-3 fmol/(cell·hr) for Prorocentrum donghaiense, and maximum to 150 fmol/(cell·hr) for Alexandrium catenella, less than 2 fmol/(cell·hr) for the diatom Skeletonema costatum using MFP as substrate (Ou et al, 2008), and 0.02-0.7 pmol/(cell·hr) (20-700 fmol/(cell·hr)) for Gymnodinium impudicum using disodium phenylphosphate as substrate (Oh et al, 2010). The APA levels of 4.76-46.4 fmol/(cell·hr) for C. marina in this study were far less than those reported for dinoflagellates species A. catenella (Jauzein et al, 2010;Ou et al, 2008) and G. impudicum (Oh et al, 2010), however much high than those reported for P. donghaiense and S. costatum (Ou et al, 2008). APA levels for H. akashiwo were comparable to those of P. donghaiense and S. costatum (Ou et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that many dinoflagellate species can effectively utilize a variety of both inorganic and organic compounds as phosphorus sources (Matsuda et al, 1999;Oh et al, 2002Oh et al, , 2010Huang et al, 2005;Yamaguchi et al, 2005). However the raphidophytes, such as Chattonella ovata, F. japonica, and H. akashiwo, have been shown not growing on phosphomonoesters other than nucleotides (Yamaguchi et al, 2005(Yamaguchi et al, , 2008.…”
Section: Discussionmentioning
confidence: 99%
“…A trend of increasing N:P ratios has been reported for Chesapeake Bay (Fisher et al, 1992), the northern Red Sea (Li et al, 1998), the South Sea of Korea (Oh et al, 2010), and the Seto Inland Sea (Oh et al, 2005). Chinese coastal waters have also been experiencing P limitation over the last two decades (Huang et al, 2007;Wang et al, 2008;Dong et al, 2010), and the average N:P ratio is high.…”
Section: Introductionmentioning
confidence: 88%